2016
DOI: 10.1155/2016/9587020
|View full text |Cite
|
Sign up to set email alerts
|

Rice Germosprout Extract Protects Erythrocytes from Hemolysis and the Aorta, Brain, Heart, and Liver Tissues from Oxidative Stress In Vitro

Abstract: Identifying dietary alternatives for artificial antioxidants capable of boosting antihemolytic and antioxidative defense has been an important endeavor in improving human health. In the present study, we studied antihemolytic and antioxidative effects of germosprout (i.e., the germ part along with sprouted stems plus roots) extract prepared from the pregerminated rice. The extract contained considerable amounts of antioxidant β-carotene (414 ± 12 ng/g of extract) and phytochemicals such as total polyphenols (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…These indicated that all doses of PN and ascorbic acid can protect hemolysis from H 2 O 2 -induced oxidative stress on intact sheep erythrocyte. Like other studies, herbal plants and plant-derived antioxidant, such as flavonoids, orientin, and luteolin, have been used to alleviate oxidative stress on erythrocyte [16, 22, 23]. PN also has antioxidative effect to protect hemolysis corresponded to our previous studies that claim an antioxidative property of PN on endothelial stress and oxidative stress induced by apoptosis [13].…”
Section: Resultsmentioning
confidence: 63%
“…These indicated that all doses of PN and ascorbic acid can protect hemolysis from H 2 O 2 -induced oxidative stress on intact sheep erythrocyte. Like other studies, herbal plants and plant-derived antioxidant, such as flavonoids, orientin, and luteolin, have been used to alleviate oxidative stress on erythrocyte [16, 22, 23]. PN also has antioxidative effect to protect hemolysis corresponded to our previous studies that claim an antioxidative property of PN on endothelial stress and oxidative stress induced by apoptosis [13].…”
Section: Resultsmentioning
confidence: 63%
“…Extracts were then filtered, dried, and suspended in water, subjected to a bath sonicator, aliquoted, and stored at 220˚C. Antioxidant phytochemicals or radical scavenging potential of rice extract was determined, as previously described (10).…”
Section: S94 In Vitro Studymentioning
confidence: 99%
“…After deep anesthesia with pentobarbital, blood from a fresh set of rats was collected from the inferior vena cava with a heparinized syringe. Erythrocytes were washed with normal saline, and then subjected to hemolysis assay, as described previously but with slide modification (10,11). Briefly, erythrocyte suspensions (at 2% hematocrit) were incubated with or without rice (WR/GBR) extract in the absence or presence freshly prepared Fenton's reagents [H 2O2 (45 mm)1FeSO4 (2 mm)] at 37˚C for 1 h. At the end of incubation, erythrocytes were gently pelleted down by centrifuging the samples at 300 3g for 10 min.…”
Section: Erythrocyte Preparation and In Vitro Hemolysis Assaymentioning
confidence: 99%
See 1 more Smart Citation